The Impact of Cataract Surgery on Vision-Related Quality of Life and Psychological Distress in Monocular Patients - Xuepei Li; Jianqiang Lin; Zidong Chen; Guangming Jin; Danying Zheng (Journal of Ophthalmology)
Purpose. To determine the changes in vision-related quality of life and psychological distress after cataract surgery in monocular patients and to compared these with a control group of age- and gender-matched binocular patients. Methods. We enrolled 40 monocular patients and 40 binocular patients who underwent cataract surgery from August 2017 to December 2018. All participants undertook eye examinations and answered questionnaires (the National Eye Institute Visual Function Questionnaire, Self-rating Anxiety Scale, and Self-rating Depression Scale) before and after cataract surgery. Result. The monocular patients had significantly worse mean CDVA than the binocular patients before and after surgery. However, there was no significant difference between the increases gained by the two groups. Mean composite VFQ-25 scores of the monocular group were significantly lower than those of the binocular group before and after surgery, but the improvement experienced by the monocular group was statistically larger than the binocular group (37.20 ± 12.84 vs. 19.11 ± 5.13, P<0.001). Mean standard SAS scores of monocular patients were significantly higher than those of binocular controls before and after surgery, while monocular patients experienced a significant greater decline of SAS scores (−9.41 ± 5.39 VS −3.84 ± 1.61, P<0.001). Mean standard SDS scores of the monocular group were significantly higher than those of the control group before and after surgery, but the monocular group experienced a significantly greater decline of SDS scores following cataract surgery (−11.91 ± 6.38 VS −4.78 ± 1.79, P<0.001). There was a significant correlation between the preoperative logMAR CDVA and both the postoperative logMAR CDVA (r = 0.63, P<0.001) and the changes in the logMAR CDVA (r = −0.881, P<0.001) for monocular patients. Linear regression analyses suggested that higher postoperative VFQ-25 scores had significant associations with better preoperative CDVA and the absence of systemic comorbidity (both P<0.05). Age and ocular comorbidity were significantly associated with postoperative SAS scores (both P<0.05). Age and systemic comorbidity remained significant impact factors for SDS scores (both P<0.05). Conclusion. Monocular patients reported greater improvement in vision-related quality of life and greater decline in the level of anxiety and depression than binocular control subjects, despite having similar CDVA gains after cataract surgery. We argue that it is not a better choice for monocular patients to delay cataract surgery until the cataract is very advanced. A clear understanding of the impact of cataract surgery on vision-related quality of life and psychological distress in monocular patients is needed by ophthalmologists when making surgery decision.